CALENDAR EFFECTS IN DAILY RETURNS IN INDIAN STOCK MARKET: AN ANALYSIS - Singh, Meenakshi A.; Sahu, Dhananjay (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The degree and scale of informational efficiency in stock markets are reflected in the frequency of calendar anomalies in general. Global stock markets experience a variety of oddities, and they differ from one nation to the next. Market players are constantly on the edge of exploiting stock market inefficiencies to produce extraordinary returns. Anomalies by day of the week significantly increase the degree of inefficiencies and distort the market. Using daily values from the BSE Sensex benchmark index from April 2015 to March 2020, the current study investigates whether the day of the week has an impact on daily returns in the Indian stock market. The GARCH model-based empirical analysis claim that the Indian stock market exhibits day-of-the-week abnormalities. By timing their investment actions correctly, market players can increase their average return and are expected to develop investment strategies to outperform the market. The results are useful, especially for small investors who are making decisions on when to enter and quit the financial market.